2022
DOI: 10.3389/fnut.2022.1024820
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the extraction, chemical composition, therapeutic potential, and delivery of cardamom phytochemicals

Abstract: Dietary phytochemicals including plant-derived alkaloids, carotenoids, organosulfur compounds, phenolics, and phytosterols, are health-promoting bioactive compounds that help in the prevention and mitigation of chronic diseases and microbial infections beyond basic nutrition supply. This article covers recent advances in the extraction, chemical composition, therapeutic potential (nutraceutical and antimicrobial), and delivery of black and green cardamom-derived phytochemicals. In recent years, advance extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The main bioactive compounds of cardamom are terpenes and phenolic compounds, which exhibit powerful antioxidant properties. Their main bioactive compounds are as follows: 1,8-cineole, α-terpinyl acetate, nerolidol, sabinene, g-terpinene, α-pinene, methyl linoleate, α-terpineol, β-pinene, n -hexadecanoic acid, and limonene [ 6 ]. 1,8-cineole and α-terpinyl acetate are the principle bioactive components in black and green cardamom ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main bioactive compounds of cardamom are terpenes and phenolic compounds, which exhibit powerful antioxidant properties. Their main bioactive compounds are as follows: 1,8-cineole, α-terpinyl acetate, nerolidol, sabinene, g-terpinene, α-pinene, methyl linoleate, α-terpineol, β-pinene, n -hexadecanoic acid, and limonene [ 6 ]. 1,8-cineole and α-terpinyl acetate are the principle bioactive components in black and green cardamom ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,8-cineole and α-terpinyl acetate are the principle bioactive components in black and green cardamom ( Table 1 ). These compounds aid in safeguarding against chronic diseases and oxidative stress (OS) [ 6 , 7 ]. Additionally, cardamom has been found to improve insulin sensitivity and glucose uptake [ 8 ], which may help to reduce the risk of type 2 diabetes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Black cardamom (Amomum subulatum) is among the world's oldest spices and has strong antioxidant properties due to the presence of its primary compounds 1,8 cineole, terpinyl acetate, pinene and pinene terpineol (Alam & Singh, 2021). Moreover, its active ingredients, especially 1,8 cineol, have also hepatoprotective, antiulcerogenic and fungi-toxin properties (Abdullah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Black cardamom ( Amomum subulatum ) is among the world's oldest spices and has strong antioxidant properties due to the presence of its primary compounds 1,8 cineole, terpinyl acetate, pinene and pinene terpineol (Alam & Singh, 2021). Moreover, its active ingredients, especially 1,8 cineol, have also hepatoprotective, antiulcerogenic and fungi‐toxin properties (Abdullah et al, 2022). Several studies on cineol and extracts rich in cineol have been reported to enhance growth performance, antioxidant status and immune response in different fish species such as Oncorhynchus mykiss (Hoseini, Taheri Mirghaed, et al, 2018; Taheri Mirghaed, Hoseini, et al, 2018), Cyprinus carpio (Fazelan et al, 2020; Hoseini, Hoseinifar, et al, 2018; Hoseini, Rajabiesterabadi, et al, 2020; Taheri Mirghaed, Fayaz, et al, 2018; Taheri Mirghaed et al, 2019) and Oreochromis niloticus (Swamy et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The biologically active compounds of cardamom include 1,8-cineole, α-terpinyl acetate (the maximum amount), sabinene, linalool acetate, nerolidol, thujene, pinene, cymene, limonene, geranial, and myrcene (Ahmad et al, 2022). Cardamom has been shown to reduce inflammation by preventing lipid peroxidation and acting as a scavenger of free radicals.…”
mentioning
confidence: 99%